Efficacy of repetitive peripheral magnetic stimulation on upper limb motor function after stroke: a systematic review and meta-analysis of randomized controlled trials - Liu, Junxia; Zhu, Meirong; Liu, Xiaoyan; Tang, Weiju; Xiang, Yunan; Xie, Yulei; Wang, Yinxu (Frontiers in Neurology, 2025)
BackgroundApproximately 50–70% of stroke survivors are left with varying degrees of limb paralysis, severely affecting their ability to perform daily activities and engage in rehabilitation. Although conventional rehabilitation interventions, such as task-oriented training and transcranial magnetic stimulation (TMS), have been widely utilized, their efficacy has been constrained by individual differences and limitations in neuroplastic activation. Repetitive peripheral magnetic stimulation (rPMS), a novel non-invasive neuromodulation technique, directly targets peripheral nerves and muscles to potentially facilitate the remodeling of motor pathways. There is a lack of evaluation regarding the effectiveness of rPMS for improving upper limb motor function and spasticity in stroke patients.MethodsRandomized controlled trials examining the effects of rPMS in post-stroke patients, published up to 20 February 2025, were searched in PubMed, Embase, the Cochrane Library, and the Web of Science. Methodological quality was evaluated using the Cochrane Collaboration tool. Meta-analyses were performed using RevMan (version 5.4). The Grading of Recommendations, Assessment, Development and Evaluation (GRADE) method was used to assess the quality of evidence.ResultsA total of 12 studies involving 492 patients were included. The results of the meta-analysis indicated that, compared to the control group, the subgroup analyses based on disease stage, stimulation frequency, coil type, stimulation duration, and stimulation intensity showed significant improvements, supported by high-quality evidence. The pooled standardized mean differences (SMDs) were as follows: disease stage, SMD = 0.69 (p = 0.006); stimulation frequency, SMD = 0.58 (p = 0.004); coil type, SMD = 0.82 (p = 0.001); stimulation duration, SMD = 0.62 (p = 0.004); and stimulation intensity, SMD = 0.79 (p = 0.002). In addition, rPMS significantly improved patients’ ability to live independently (SMD = 0.66, p <0.0001), supported by moderate-quality evidence. However, rPMS did not demonstrate a significant effect in reducing spasticity [mean difference (MD) = 0.25, p = 0.20], with this finding supported by low-quality evidence.Systematic review registrationrPMS improved upper limb motor function, activities of daily living (ADL), and self-care abilities in post-stroke patients, with good acceptability and only mild adverse reactions. Its effect on spasticity was not significant.Systematic review registrationwww.crd.york.ac.uk/prospero/, CRD420250637455.